Management of geotechnical risks of road projects using Mads-Mosar method - Benachenhou, Kamila Amel; Verdel, Thierry; Allal, Mohammed Amine; Lakermi, Anis (International Journal of Engineering and Technology, 2016)
For the last few years, roads and motorways projects have been developing in Algeria, where the risk management remains timorous. Indeed, these projects exhibit many geotechnical disorders of natural or anthropic origin, which disturb their progress. Furthermore, the latent effects of these disorders can affect the life of the works as well as the safety and comfort of the users. Therefore, this paper addresses the use of the MADS-MOSAR method as a risk assessment method that can be used in the construction area to consider a wide range of risk sources including non-geotechnical ones. This method, which is widely used in industry, is tentatively used to identify the causes and consequences of undesired geotechnical events in the case of the main slip road â€œAâ€ at the exchange of the RN02 road in Tlemcen, Algeria. The choice of this method implies first a system modelling approach and a functional analysis to inventory all possible sources of danger and all possible interactions and to perform a global risk assessment. At the end, we show the relevance of this method in the field of geotechnical risk management for road projects.